Mobility, taxation and welfare - Sami Bibi; Jean-Yves Duclos; Abdelkrim Araar (Institute for the Study of Labor (IZA), 2011)
Income mobility is often thought to equalize permanent incomes and thereby to improve social welfare. The welfare analysis of mobility often fails, however, to account for the cost of the variability of periodic incomes around permanent incomes. This paper assesses the net welfare benefit of mobility by assuming both a social aversion to inequality in permanent incomes and an individual aversion to variability in periodic incomes. The paper further investigates the combined (and comparative) impact of mobility and of the tax system (another presumed income equalizer) on the dynamics of income across time and on the inequality of income across individuals. Using panel data, we find that Canada's tax system limits significantly the redistributive impact of mobility while also lowering considerably the cost of income variability. The permanent income equalizing effect of taxes can reach up to 23 percent of mean income at the higher values of inequality aversion that we use. Globally, the net social welfare effect of both mobility and taxation is (almost always) positive and substantial, often amounting to around 30 percent of mean income. For all choices of parameter values, the tax effect exceeds by far the net effect of mobility on inequality and social welfare.
urn:nbn:de:101:1-201106202102
Keywords: D31; D63; H24; 330; mobility; social welfare; risk; income variability; inequality; permanent income